Possible Interplay Between Hospital and Community Transmission of a Novel Clostridium Difficile Sequence Type 295 Recognized by Next-Generation Sequencing. (14th April 2016) - Moloney, Geraldine; Mac Aogáin, Micheál; Kelleghan, Maureen; O'Connell, Brian; Hurley, Caroline; Montague, Elizabeth; Conlon, Mary; Murray, Helena; Rogers, Thomas R.
Abstract : OBJECTIVE: To use next-generation sequencing (NGS) analysis to enhance epidemiological information to identify and resolve a Clostridium difficile outbreak and to evaluate its effectiveness beyond the capacity of current standard PCR ribotyping. METHODS: NGS analysis was performed as part of prospective surveillance of all detected C. difficile isolates at a university hospital. An outbreak of a novel C. difficile sequence type (ST)-295 was identified in a hospital and a community hostel for homeless adults. Phylogenetic analysis was performed of all ST-295 and closest ST-2 isolates. Epidemiological details were obtained from hospital records and the public health review of the community hostel. RESULTS: We identified 7 patients with C. difficile ST-295 infections between June 2013 and April 2015. Of these patients, 3 had nosocomial exposure to this infection and 3 had possible hostel exposure. Current Society for Healthcare Epidemiology of America (SHEA)— Infectious Diseases Society of America (IDSA) surveillance definitions (2010) were considered in light of our NGS findings. The initial transmission was not detectable using current criteria, because of 16 weeks between ST-295 exposure and symptoms. We included 3 patients with hostel exposure who met surveillance criteria of hospital-acquired infection due to their hospital admissions. CONCLUSION: NGS analysis enhanced epidemiological information and helped identify and resolve an outbreak beyond the capacity of standard PCR ribotyping. In this cluster of cases, NGS was used to identify a hostel as the likely source of community-based C. difficile transmission. Infect Control Hosp Epidemiol 2016;37:680–684